Forming a TED talks sphere for convenient search. Issue 2 (29th April 2020) - Shih, Chia-Hui; Li, Han-Lin; Hu, Chih-Chien; Lin, Bertrand M.T.
Abstract : Purpose: TED (Technology, Entertainment, Design, www.ted.com/ ) Talks has been one of the most popular video systems. However, the current TED Talks system expressed its inquired videos as in a two-dimensional (2D) table, which is inconvenient for searching the relationships among videos and tags. This study converts the TED Talks table into a sphere by using optimization techniques to help users search for preferred videos. Design/methodology/approach: There are five phases in this study as follows. Phase 1: Reorganize data of 36 tags and 108 videos; Phase 2: Allocate tags on the TED sphere; Phase 3: Allocate videos on the TED sphere; Phase 4: Develop an online interactive TED retrieval system; and Phase 5: Perform survey and evaluation. Findings: One survey demonstrated that the TED Talks sphere is more convenient for searching videos, as it is more user-friendly because of its graphical user interface, more convenient to use, more useful for retrieving information and can facilitate a more responsive search for users' preferred videos. Research limitations/implications: The numbers of tags and videos able to be displayed on a sphere is limited by the capacity of an optimization software and hardware. Practical implications: The proposed sphere system can be used by a large number of users of TED Talks groups. Social implications: This sphere systems can also be applied to other fields which use 2D forms to display the relationships among objects. Originality/value: This study uses an optimization method to convert a 2D form into a 3D sphere to highlight the relationships among numerous objects.